P124 Neuroventilatory uncoupling during cycle and treadmill exercise in COPD. (16th November 2010) - Jolley, C J; Luo, Y M; Steier, J; Rafferty, G; Polkey, M I; Moxham, J
Abstract : Background: It is widely accepted that neuroventilatory uncoupling drives breathlessness in COPD. COPD patients are more likely to stop exercising because of breathlessness during treadmill exercise than whilst cycling. Aim: To test the hypothesis that patients exhibit higher levels of neuroventilatory uncoupling during treadmill exercise than whilst cycling. Methods: Diaphragm electromyogram (EMGdi ) and parasternal intercostal muscle EMG (EMGPS ) activity were recorded in 12 COPD patients (mean (SD) age 66.7 (7.0) years, FEV1 38.7 (14.5)% predicted, 11 male), during incremental cycle and treadmill exercise to exhaustion. For each muscle, the mean peak root mean square (RMS) EMG per breath over the final 30 s of each minute was normalised to peak RMS EMG recorded during maximal inspiratory manoeuvres, and corrected for inspiratory time and respiratory rate (EMGdi index, EMGPS index). Borg breathlessness was assessed every minute and at exhaustion. Results: EMGPS index and EMGPS activity per unit ventilation (EMGPS index/VE ) were higher at exhaustion during treadmill exercise (Abstract P124 Table 1 ). A higher VE at exhaustion whilst cycling approached statistical significance. EMGdi index and breathlessness were not significantly different at exhaustion when exercise modes were compared. Conclusion: A higher EMGPS index/VE and lower VE at exhaustion during treadmill exercise suggest that neuroventilatory uncoupling is greater than during cycle exercise. This did not translate to greater breathlessness during treadmill exercise in this study, but warrants further investigation in a larger group of patients.